Evaluation of the protective roles of alpha-lipoic acid supplementation on nanomaterial-induced toxicity: A meta-analysis of in vitro and in vivo studies - Luo, Xiaogang; Xie, Dongli; Wu, Tong; Xu, Wei; Meng, Qingyang; Cao, Kangli; Hu, Jianchen (Frontiers in Nutrition, 2022)
Extensive exposure to nanomaterials causes oxidative stress and inflammation in various organs and leads to an increased risk of adverse health outcomes; therefore, how to prevent the toxic effects are of great concern to human. Alpha-lipoic acid (ALA) has anti-oxidant and anti-inflammatory activities, suggesting it may be effective to prevent nanomaterial-induced toxicity. However, the results obtained in individual studies remained controversial. We aimed to comprehensively evaluate the effects of ALA supplementation on nanomaterial-induced toxicity by performing a meta-analysis. Databases of PubMed, EMBASE and Cochrane Library were searched up to May 2022. STATA 15.0 software was used for statistical analysis. Twelve studies were included. Meta-analysis of eight in vivo studies showed ALA supplementation could exert signiﬁcant effects on nanomaterial-induced oxidative stress (by reducing MDA, ROS and increasing GSH, CAT, GPx and SOD), inflammation (by downregulating NO, IgG, TNF-α, IL-6 and CRP), apoptosis (by activation of pro-apoptotic caspase-3), DNA damage (by a reduction in the tail length) and organ damage (by a decrease in the liver biomarker ALT and increases in brain neuron biomarker AChE and heart biomarker CPK). Pooled analysis of four in vitro studies indicated ALA intervention increased cell viability, decreased ROS levels, inhibited cell apoptosis and chelated metal ions. Subgroup analyses revealed changing the levels of GSH, IL-6 and metal ions were the main protective mechanisms of ALA supplementation because they were not changed by any subgroup factors. In conclusion, ALA supplementation may represent a potential strategy for the prevention of the toxicity induced by nanomaterials.